Hadis tentang Bersuci menurut Teologi dan Kesehatan - Indah Haspari; Busro; Wawan Hernawan (Gunung Djati Conference Series, 2022)
This study aims to discuss the hadith about purification. This study uses a qualitative approach by applying the descriptive-analytical method. The formal object of this research is the science of hadith from the point of view of theology and health sciences, while the material object is the hadith about purification in the history of Bukhari no. 132. The results and discussion of this study indicate that the status of the hadith is authentic with the qualifications of maqbul ma'mul bih for the practice of Islam regarding purification from a theological point of view in the inner sense and health science in the outer sense. This study concludes that the hadith narrated by Bukhari no. It is relevant to be used as inspiration to develop Islamic teachings about purification from a holistic point of view.